Water quality indices - Abbasi, Tasneem; Abbasi, S. A. (Shahid A.). (Amsterdam : Elsevier, 2012)
'This book covers water quality indices (WQI) in depth - it describes what purpose they serve, how they are generated, what are their strengths and weaknesses, and how to make the best use of them. It is a concise and unique guide to WQIs for chemists, chemical/environmental engineers and government officials. Whereas it is easy to express the quantity of water, it is very difficult to express its quality because a large number of variables determine the water quality. WQIs seek to resolve the difficulty by translating a set of a large number of variables to a one-digit or a two-digit numeral. They are essential in communicating the status of different water resources in terms of water quality and the impact of various factors on it to policy makers, service personnel, and the lay public. Further they are exceedingly useful in the monitoring and management of water quality.'-- Back cover.
Keywords: Water quality